The Effect of Leadership Style on Loyalty and Work Motivation in Bumimas Permata Group Company - Fuidy Luckman; Edison C. Sembiring; Toto Hardiyanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine and analyze the influence of leadership style on loyalty and work motivation in Bumimas Permata Group Companies. This research design is a causal study (cause and effect) with quantitative research. The target population in this study were 121 employees of the Bumimas Permata Group company, namely they were either directly or indirectly under the leadership of the researcher. The researcher uses the Non Propability Sampling method by using a saturated sampling technique on the census of 121 employees within the Bumimas Permata Group company. Based on the results of the analysis and discussion shows that there is a significant influence of leadership style on work loyalty, there is a significant influence of leadership style on work motivation, there is a significant influence of work loyalty on work motivation and there is an influence of leadership style on work motivation with work loyalty as a mediating variable in Bumimas Permata Group company.